Policy responses to terms of trade shocks - Pierre Jacquet; Alexis Atlani; Marwan Lisser (Fondation pour les études et recherches sur le développement international (FERDI), 2017)
Terms-of-trade shocks are important determinants of long-term growth in commodity-rich developing countries. Transforming commodity assets into engines of development requires confronting two interrelated challenges: a long-term one of moving from commodity dependency to a diversified productive economy, a short-term one of managing commodity price volatility. Both challenges call for appropriate policies. The complexity of the channels of transmission reviewed in the existing literature vouches for these policies to be country and commodity specific and for implementation to receive at least as much attention as recommendations – especially in view of the historically documented incentives to deviate from recommendations and conduct poor policies. Our paper suggests that the best general advice is to highlight a few robust principles, to reflect on the conditions for their implementation, and to empower local institutions while strengthening research capacities so that the understanding of policy challenges and principles is locally owned and may better inspire policies and institutional building.
Keywords: 330